Analysis of Phenolic and Tannin Contents in the Methanol Extract of Sweet and Sour Star Fruit Plants (Averrhoa carambola L) Leaves Commonly Used as Raw Materials of Lawar (A Balinese Traditional Food) - Astiti, Ni Putu Adriani; Sudirga, Sang Ketut; Ramona, Yan (Advances in Tropical Biodiversity and Environmental Sciences, 2019)
Lawar , a special Balinese food made of leaves of star fruit plant, is commonly served in any Balinese traditional events, such as temple festival or wedding parties. The leaves of sweet and sour star fruit plant are used to make this traditional food. In this research, phenolic and tannin content of leaves of these types of plant were analyzed with a view to investigate their potential as antioxidant source. Phenolic compound has been well known to have antioxidant activity by neutralizing free radicals and stabilizing singlet oxygen.  This compound has capacity to reduce free radicals by chelating metal ions or inhibiting enzymatic system, such as cyclo-oxygenase, mono-oxygenase or xanthine oxidase that catalyze formation of free radicals. [4] reported that plants with high content of phenolic compounds tend to have high nutritious and antioxidant activities Tannin is a compound belongs to polyphenolic group. Such compound is abundantly found in any plants. This compound has capacity to bind proteins, alkaloid, and gelatin. In human body, this compound play a very complex role, such as chelating metal ions, precipitating proteins, and functioning as biological antioxidant. The results of this study showed that the phenol content of sour and sweet star fruit plants were 2830.99/100 mg GAE and 1959.77/100 mg GAE, respectively, while the tannin content of these two plants were 18810.43 mg/100 gr TAE and 11035.75 mg/100 gr TAE, respectively, indicating that the leaves of sour star frit plant had better antioxidant activity than the sweet one.